The Role of Teacher Professionalism in Improving Student Motivation and Learning Quality at MI Al Islamiyah Bandarsakti - Khoerudin, Afip; Mantik, Aliyah (IJoIS: Indonesian Journal of Islamic Studies, 2025)
In MI Al Islamiyah Bandarsakti, there is a problem of low student motivation which is reflected in the number of students who have not reached the Minimum Completeness Criteria (KKM). This low learning motivation is influenced by several factors such as the less-than-optimal role of the teacher in managing the class and delivering the material, as well as the limited learning facilities available. Many students show a lack of enthusiasm in participating in learning and have difficulty in understanding the material presented, which has an impact on unsatisfactory learning outcomes. This study aims to identify the extent to which teacher professionalism affects student learning motivation and the quality of learning outcomes at MI Al Islamiyah Bandarsakti, as well as analyze the factors that shape teacher professionalism in improving learning quality. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation and document analysis. Data were analyzed using thematic analysis method and validated through triangulation and member checking. The results showed that teacher professionalism has a significant influence on student motivation and learning quality. Teachers who have good pedagogical competence, effective communication skills, and adequate classroom management skills are proven to increase students’ interest and engagement in learning.